DYSTOCIA DUE TO UNILATERAL SHOULDER FLEXION AND ITS COMPLICATION IN CROSSBRED COW - PATEL, M P; PATEL, P B; JOSHI, N A; ANKUYA, K J; SUTHAR, B N (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to unilateral shoulder flexion in a crossbred cow was resolved with fetotomy andmutation.
Keywords: Dystocia; Unilateral shoulder flexion